Assessment of surface water management institutions: a case of public irrigation schemes in northern Algeria. Issue 2 (10th January 2022) - Oulmane, Amine; Kechar, Abdelhadi; Benmihoub, Ahmed; Amine Benmehaia, M.
Abstract: The pressure on water resources that Algeria encounters is due to the scarcity and the water demand increase by different sectors of activity. This induces managers to reconsider the traditional supply management approach. The new water policies aim to adopt water demand management by improving the efficiency of its use in the agricultural sector, which consumes more than 59% of freshwater withdrawals. Economic, regulatory, and voluntary instruments have been adopted for better governance of water resources. This study aims to (i) define institutional arrangements on the exploitation of surface water in large irrigation schemes in Algeria and (ii) assess the effectiveness of the current water management instruments. Findings from farmers' and water distribution agencies' surveys suggest that objectives expected by the application of the different economic instruments are far from being achieved. Moreover, the absence of effective executive agencies for the implementation of regulations suggests that an improvement in the performance of public administration is necessary to achieve better governance of irrigation water in Algeria. At the local level, and despite a lack of farmers' will to formally engage in a collective of farmers, they organize themselves around informal arrangements to overcome the challenges associated with water scarcity. HIGHLIGHTS: The desired objectives of cost recovery and reducing the pressure on the resource are not achieved. Quota policy leads to a greater pressure on groundwater resources. A greater consideration of groundwater is necessary. The enforcement of regulatory instruments is not effective. The improvement in the performance of public administration is necessary to achieve better governance of irrigation water in Algeria.